The Urgency of Learning the Values of Worship in Madrasah Ibtidaiyah - Astuti, Hepy Kusuma; Anwar, Saepul (EDUCAN : JURNAL PENDIDIKAN ISLAM, 2024)
The values of worship are very important to be instilled, especially in elementary school or Madrasah age children. Moreover, with the rapid development of the digital world today, Madrasas must be able to adapt to various problems that faced from the moral crisis due to excessive use of gadgets. This short article tries to explore the urgency of inculcation of religious values, especially in Madrasah Ibtidaiyah or elementary schools. The method used is descriptive qualitative with a conceptual approach. The results of the discussion reveal that the cultivation of worship values is very urgent to do to face the current digitalization 4.0. This is to strengthen children's religious character and keep adapting to the digital world. The inculcation of these values is carried out by example, participation, wisdom in stories, habituation and discipline. The values of worship that can be instilled in Madrasas are the value of piety, the value of discipline, the value of honesty, and the value of patience.